Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5750/ejpch.v5i3.1298
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in a mixed ethnic population after myocardial infarction

Abstract: Background: Although South Asian people are a significant ethnic group at increased risk of coronary heart disease and high mortality rates and experience greater delays with respect to diagnosis, referral and treatment, comparatively little is known about their quality of life during recovery from a myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Following MI, patients frequently report poor health related quality of life (HRQoL), which may not recover [ 5 ], and is independently associated with higher rates of death at 1 year [ 6 , 7 ]. Poor HRQoL is more commonly reported among women [ 8 , 9 ], older people with frailty [ 5 , 10 ], non-white ethnicity [ 11 ], and in those that experience bleeding complications relating to dual anti-platelet therapy [ 12 ]. Several previous studies have looked at individual chronic health conditions and their impact on health-related quality of life in MI survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Following MI, patients frequently report poor health related quality of life (HRQoL), which may not recover [ 5 ], and is independently associated with higher rates of death at 1 year [ 6 , 7 ]. Poor HRQoL is more commonly reported among women [ 8 , 9 ], older people with frailty [ 5 , 10 ], non-white ethnicity [ 11 ], and in those that experience bleeding complications relating to dual anti-platelet therapy [ 12 ]. Several previous studies have looked at individual chronic health conditions and their impact on health-related quality of life in MI survivors.…”
Section: Introductionmentioning
confidence: 99%
“…M. Dempster and Donnelly (2000) reported there are increasing of correlations between the MacNew scales and relevant scales on the SF-36 in term of grouping items grouping when compared to the grouping of items suggested by Valenti, Lim, Heller, and Knapp (1996). As a result, the MacNew questionnaire is a reliable and valid method of assessing changes in Whereas in the Asian countries, the result showed majority of the population are men and older than 60 or elderly whereas women the most suffer that can be viewed by the score of HRQOL (Henriksson et al, 2014;Mollon & Bhattacharjee, 2017;Rančić et al, 2013;Tegn et al, 2018;Webster, Thompson, Larkin, Mayou, & Martin, 2017). Even though, on those studies reported that average total sample of the patients is under 55 age years old.…”
Section: Disease Specific Instrumentmentioning
confidence: 99%
“…In addition, most of them suffer with symptom of pain or discomfort while many comorbidities give more burden of patients such as diabetes mellitus and prior cardiac event or other cardiac disease. On some longitudinal studies, the HRQOL increased and mental domain or depression decreased (Le, Dorstyn, Mpfou, Prior, & Tully, 2018;Webster et al, 2017).…”
Section: Disease Specific Instrumentmentioning
confidence: 99%